2019
DOI: 10.1007/s11103-019-00873-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel transcriptional responses to heat revealed by turning up the heat at night

Abstract: Key message The circadian clock controls many molecular activities, impacting experimental interpretation. We quantify the genome-wide effects of time-of-day on the heat-shock response and the effects of “diurnal bias” in stress experiments. Abstract Heat stress has significant adverse effects on plant productivity worldwide. Most experiments examining heat stress are performed during daytime hours, generating a ‘diurnal bias’ in the pathways and regulatory mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 108 publications
4
52
0
Order By: Relevance
“…A similar response has been observed for DREB2B, and overexpression of the rice OsDREB2A and OsDREB2B showed improved plant tolerance to drought, suggesting a conservation of the regulatory mechanisms across plant species [104,105]. Other DREB TFs, designated CBFs, have been shown to be regulated by cold, high ambient temperatures, and heat stress, implicating them as important regulators linking the clock to temperature stress response mechanisms [43,44,50,58].…”
Section: Time Of Day and Other Clock-regulated Heat Responsive Transcsupporting
confidence: 61%
See 2 more Smart Citations
“…A similar response has been observed for DREB2B, and overexpression of the rice OsDREB2A and OsDREB2B showed improved plant tolerance to drought, suggesting a conservation of the regulatory mechanisms across plant species [104,105]. Other DREB TFs, designated CBFs, have been shown to be regulated by cold, high ambient temperatures, and heat stress, implicating them as important regulators linking the clock to temperature stress response mechanisms [43,44,50,58].…”
Section: Time Of Day and Other Clock-regulated Heat Responsive Transcsupporting
confidence: 61%
“…Together, warm temperatures impact multiple levels of gene regulation, including alternative splicing, post-translation, and protein abundance [12,34,41,42]. More recently, it has been shown that the impact on the transcript abundance of clock genes following a 1 h exposure to 30 • C differs depending on the time of day [43]. Circadian gating (controlling the magnitude or the occurrence of a response based on time of day) of cold responses for clock and clock-controlled genes have been previously reported [44].…”
Section: Time Of Day (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gene ontology enrichment processes for the genes in these daytime phased modules included photosynthesis and abiotic stress response (Dataset S3). However, it should be noted that in general, evening phased genes are likely to be greatly understudied because most experiments are performed during the day (45).…”
Section: Discussionmentioning
confidence: 99%
“…This led us to wonder whether there is any indication that these pattern changes may contribute to new temporal responses to environmental stimuli such as abiotic stress. The gated stress response has been characterized in several plant species including Arabidopsis, poplar, rice and B. rapa (26,(42)(43)(44)(45). If a time-ofday dependent stress responsive gene in Arabidopsis now has two copies in B. rapa with altered expression patterns does this result in an expanded stress response window or does one copy retain stress response while the other loses it?…”
Section: Do Retained Multi-copy Circadian Regulated Genes Exhibit Genmentioning
confidence: 99%